High-strength heat-preservation and heat-insulation building coating and preparation method thereof
By adopting high-strength thermal insulation and thermal insulation building coatings, and using the combination of modified aluminum silicate fiber and mullite powder, the problem of poor thermal insulation performance of existing coatings is solved, and better thermal insulation effect and hardness performance are achieved.
Patent Information
- Application Number
- CN202510324993.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing water-based architectural paint has poor thermal insulation performance after coating, which affects the thermal insulation performance and indoor comfort of building walls.
A high-strength thermal insulation building coating is used, which consists of polyurethane resin, phenolic resin, modified aluminum silicate fiber dissolving solution, mullite powder, etc. It forms tiny voids and thermal insulation layer through alkali etching treatment of modified aluminum silicate fibers and physical filling of mullite powder, thereby improving the dispersion and compatibility of the coating.
It significantly improves the insulation performance and hardness of building paints, forms a continuous insulation layer, and enhances the insulation effect and service life of the building.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building coatings, in particular to a high-strength thermal insulation building coating and a preparation method thereof. Background Art
[0002] Paint applied to the surface of an object can bond well with the base material and form a complete and tough protective film. It is called architectural coating. The role of coating can be summarized into three aspects: protective role, decorative role, and special functional role.
[0003] A patent document with publication number "CN 108300152 A" discloses a method for preparing a building coating. The coating includes the following components: 50-70 parts of polybutadiene epoxy resin, 2-6 parts of additives, 5-15 parts of bentonite, 2-5 parts of quicklime, 1-3 parts of polyurethane rigid foam powder, 4-8 parts of propyl acetate, 1-3 parts of dispersant, and 3-5 parts of thickener. The coating has simple ingredients, convenient configuration, and low cost. It has good water resistance and stain resistance, is economical and environmentally friendly, has stable performance, and has a long service life, and can better meet the needs of manufacturers.
[0004] Although the water-based architectural coating prepared in the above patent document has the characteristics of stable performance and long service life, its own thermal insulation is relatively poor. After the architectural coating is applied, it affects the thermal insulation performance of the building wall to a certain extent, thereby affecting the comfort of indoor personnel. Based on this, the present invention provides a high-strength thermal insulation architectural coating and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength thermal insulation architectural coating and a preparation method thereof. The water-based coating prepared by the present invention not only has good thermal insulation performance, but also has the characteristics of high strength.
[0006] To achieve the above object, the present invention provides the following technical solutions: A high-strength thermal insulation building paint is composed of the following raw materials in parts by weight: 80-100 parts of polyurethane resin, 15-25 parts of phenolic resin, 20-30 parts of water, 2-4 parts of perfluoropropyl vinyl ether, 8-10 parts of thickener, 8-12 parts of functional additive, 5-8 parts of crosslinking agent, 4-6 parts of film former, 1.2-1.8 parts of isolating agent, 0.3-0.6 parts of reinforcing agent and 0.2-0.3 parts of catalyst.
[0007] The present invention is further configured as follows: the preparation method of the functional additive comprises the following steps: Step 1, soaking the modified aluminum silicate fiber in a 0.1-0.12 mol / L hydrogen chloride aqueous solution for 6-8 hours, completing the pretreatment of the modified aluminum silicate fiber after soaking, and continuing to soak the modified aluminum silicate fiber in a 1-1.2 mol / L caustic soda solution, and during the soaking process, placing it in an oven at 80-100°C for 6-8 hours, and obtaining the modified aluminum silicate fiber treated with alkali etching after high temperature soaking; Step 2: Cut the modified aluminum silicate fiber obtained by alkali etching in step 1 into pieces, wash with boiling water for 40-60 minutes, and then place it in an oven at 60°C for drying for 2-2.5 hours. Mix dimethylacetamide as a solvent with the small pieces of modified aluminum silicate fiber at a solid-liquid ratio of 1:30-40, maintain the solvent temperature at 70°C and dissolve for 50-70 minutes. After dissolution, a modified aluminum silicate fiber solution is obtained, which is the functional additive.
[0008] The present invention is further configured as follows: the preparation method of the modified aluminum silicate fiber is: selecting aluminum silicate fibers with a fiber length of 1400-1500 μm and a pH value of 8-9, placing the aluminum silicate fibers in a sodium hydroxide solution with a solid-liquid ratio of 1:30-35, subjecting the mixed solution to high-temperature treatment, wherein the high-temperature treatment temperature is controlled at 80-90°C, and then placing the mixed solution in an oven, controlling the temperature to 50-60°C for drying for 1-1.5 hours, washing with water for standby use after the drying treatment is completed, thereby obtaining a base material, and then placing the base material in an acrylamide-methylpropane sulfonic acid reaction solution at a solid-liquid ratio of 1:3-4, bathing the solution in water at 75-85°C for 10-12 minutes, washing with water, and freeze-drying the resulting product, which is the modified aluminum silicate fiber.
[0009] The present invention is further configured as follows: the preparation method of the isolation agent is: adding mullite powder as powder to a mixing device, adding 1-1.5 times of water and 0.2-0.3 times of water glass to the mixing device, starting the mixing device for high-speed stirring for 15-20 minutes, and after the mixing device obtains slurry, pouring the slurry into a 15mm×15mm×1mm mold for molding preparation, drying and curing the mold in batches, placing multiple batches of molds in a drying box set at 50-60°C for 48 hours for drying and curing, and after drying and curing, placing the obtained dried and cured material in a kiln at 1300°C for firing for 8-10 hours to finally obtain a flaky solid raw material.
[0010] The present invention is further configured as follows: adding solid raw materials into the grinding chamber of a ball mill, starting the ball mill and continuously ball milling for 30-40 minutes at a rotation speed of 400-600 r / min, placing the powder obtained after ball milling in a mixing device, adding water 2-3 times the amount of the powder, then starting the mixing device and stirring at a low speed for 5-8 minutes, and after stirring, the powder and water are evenly mixed to obtain a mud material, which is the isolation agent.
[0011] The present invention is further configured as follows: the preparation method of the thickener is: diatomaceous earth, sodium polyacrylate, ethoxylated carbamate and agar are mixed and poured into a mixing device and stirred at a low speed for 15-20 minutes. After the stirring is completed, a 300-mesh filter cloth is used to filter and obtain the thickener.
[0012] The present invention is further configured as follows: the cross-linking agent is selected from any one of ferric chloride aqueous solution, tetramethylethylenediamine solution, and hydrochloric acid solution; and the strengthening agent is selected from any one of polyacrylate and methacrylate.
[0013] The present invention is further configured as follows: the catalyst is selected from any one of hydroxyphenyl triazine, benzodiazepine, and hydroxybenzimidazole, and the film-forming agent is selected from any one of trimethylsiloxysilicate, acrylic resin, and dimethylsiloxane copolymer.
[0014] The present invention is further configured as follows: the catalyst is processed by adding the catalyst raw material into a high-speed disperser, then controlling the speed of the high-speed disperser to 800-900r / min, the time to 5-8min, and then performing a pressure reduction treatment, the pressure reduction speed is controlled at 4-6kPa / min until it returns to a normal pressure state, thereby obtaining a catalyst.
[0015] The second aspect of the present invention also provides a method for preparing a high-strength thermal insulation building coating, comprising the following steps: mixing a polyurethane resin and a phenolic resin and then adding the mixture to an internal mixer, preheating the mixture after adding the mixture to the internal mixer, the preheating temperature is 130-150°C, keeping the mixture warm for 2-4 hours after the preheating is completed, running the internal mixer for heat preservation and mixing for 2-2.5 hours after the heat preservation, then stopping the machine and continuing to heat up to 180-190°C, and continuing to heat and mix for 3-3.5 hours after the temperature is raised, the resulting coating base material is used for standby, and the mixed thickener, functional additive and cross-linking agent are heated in a constant temperature water bath at 90-100°C, and the constant temperature heating time is 2 hours. The mixing time is set to 30-40 minutes, thereby obtaining the additive, and then the coating base material, additive and other raw materials are weighed as needed, and each raw material is put into an internal mixer. Each raw material is preheated to 140-160°C in the internal mixer. After the preheating is completed, the internal mixer is set to a speed of 300-400r / min and started. After heat preservation and mixing for 1-1.5 hours, a preliminary mixture is obtained. After mixing in the internal mixer, the internal mixer is evacuated to a vacuum state, and the internal pressure of the internal mixer is maintained at 30-32kPa. After pressure maintenance and defoaming for 40-45 minutes, normal pressure is restored, and high-strength thermal insulation building coatings are obtained after natural cooling at room temperature.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. After the modified aluminum silicate fiber is prepared into a dissolved liquid, when the modified aluminum silicate fiber dissolved liquid is mixed with other raw materials to prepare a coating and is coated on the surface of a building, its fiber structure will form tiny gaps and a heat-insulating layer in the coating, effectively preventing the conduction and radiation of heat, thereby improving the dispersibility and compatibility of the building coating, allowing the coating to be more evenly coated on the surface of the building, forming a continuous heat-insulating layer, and having a good thermal insulation effect.
[0017] 2. The present invention prepares mullite powder into mud as an isolating agent and mixes it with other raw materials. After the mullite mud is applied and dried, it fills the gaps and defects in the coating through physical filling effect, making the coating structure more compact and uniform, thereby improving its hardness. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Example 1
[0020] A high-strength thermal insulation building paint is composed of the following raw materials in parts by weight: 80 parts of polyurethane resin, 15 parts of phenolic resin, 20 parts of water, 2 parts of perfluoropropyl vinyl ether, 8 parts of thickener, 8 parts of functional additive, 5 parts of cross-linking agent, 4 parts of film-forming agent, 1.2 parts of isolating agent, 0.3 parts of reinforcing agent and 0.2 parts of catalyst.
[0021] The preparation method of the functional additive comprises the following steps: Step 1, soaking the modified aluminum silicate fiber in a 0.1 mol / L hydrogen chloride aqueous solution for 6 hours, completing the pretreatment of the modified aluminum silicate fiber after soaking, and continuing to soak the modified aluminum silicate fiber in a 1 mol / L caustic soda solution. During the soaking process, the fiber is placed in an oven at 80°C for 6 hours, and after high-temperature soaking, the modified aluminum silicate fiber treated with alkali etching is obtained; Step 2: Cut the modified aluminum silicate fiber obtained by alkali etching in step 1 into pieces, wash with boiling water for 40 minutes, and then place in an oven at 60°C for 2 hours to dry, and mix dimethylacetamide as a solvent with the small pieces of modified aluminum silicate fiber obtained at a solid-liquid ratio of 1:30, and keep the solvent temperature at 70°C for 50 minutes to dissolve, and obtain a modified aluminum silicate fiber solution after dissolution, which is the functional additive.
[0022] Furthermore, the preparation method of modified aluminum silicate fiber is as follows: select aluminum silicate fiber with a fiber length of 1400μm and a pH value of 8, place the aluminum silicate fiber in a sodium hydroxide solution with a solid-liquid ratio of 1:30, and perform high-temperature treatment on the mixed solution. The high-temperature treatment temperature is controlled at 80°C, and then placed in an oven and dried at 50°C for 1h. After the drying treatment is completed, wash with water for use, thereby obtaining a base material, and then place the base material in an acrylamide-methylpropane sulfonic acid reaction solution at a solid-liquid ratio of 1:3, and water bath it at 75°C for 10 minutes. After washing with water and freeze-drying, the obtained product is the modified aluminum silicate fiber.
[0023] Furthermore, the preparation method of the isolation agent is as follows: add mullite powder as powder to a mixing device, add 1 times the amount of water and 0.2 times the amount of water glass to the mixing device, start the mixing device for high-speed stirring for 15 minutes, and after the mixing device obtains slurry, pour the slurry into a 15mm×15mm×1mm mold for molding preparation, dry and solidify the mold in batches, place multiple batches of molds in a drying oven set at 50°C for 48 hours for drying and solidification, and after drying and solidification, place the obtained dried and solidified material in a kiln at 1300°C and burn it for 8 hours to finally obtain a flaky solid raw material.
[0024] Furthermore, the solid raw material is added into the grinding chamber of the ball mill, the ball mill is started and the ball mill is continuously milled for 30 minutes at a speed of 400 r / min, the powder obtained after the ball milling is placed in a mixing device, water twice the amount of the powder is added, and then the mixing device is started at a low speed and stirred for 5 minutes. After stirring, the powder and water are evenly mixed to obtain a mud material, which is the isolation agent.
[0025] Furthermore, the preparation method of the thickener is: diatomaceous earth, sodium polyacrylate, ethoxylated carbamate and agar are mixed and poured into a mixing device and stirred at a low speed for 15 minutes. After the stirring is completed, a 300-mesh filter cloth is used to filter to obtain the thickener.
[0026] The cross-linking agent is ferric chloride aqueous solution, and the reinforcing agent is polyacrylate.
[0027] The catalyst is hydroxyphenyl triazine, and the film-forming agent is trimethylsiloxysilicate.
[0028] Furthermore, the catalyst is processed as follows: the catalyst raw material is added into a high-speed disperser, and then the speed of the high-speed disperser is controlled to 800 r / min, the time is controlled to 5 min, and then the pressure is reduced, and the pressure reduction rate is controlled at 4 kPa / min until it returns to normal pressure, thereby obtaining the catalyst.
[0029] In addition, the present embodiment also provides a method for preparing the above-mentioned high-strength thermal insulation building coating, comprising the following steps: mixing the polyurethane resin and the phenolic resin and adding them to an internal mixer, preheating the mixture after adding them to the internal mixer, the preheating temperature is 130°C, keeping warm for 2 hours after the preheating is completed, running the internal mixer for heat preservation and mixing for 2 hours after heat preservation, then stopping and continuing to heat up to 180°C, and continuing to keep warm and mix for 3 hours after heating, the resulting coating base material is used for standby, and the mixed thickener, functional additive and cross-linking agent are heated in a constant temperature water bath at 90°C, and the constant temperature heating time is set to The temperature is set to 30 minutes, thereby obtaining the additive, and then the coating base material, additive and other raw materials are weighed as needed, and each raw material is put into an internal mixer. Each raw material is preheated to 140°C in the internal mixer. After preheating, the internal mixer is set to a speed of 300r / min and started. After heat preservation and mixing for 1 hour, a preliminary mixture is obtained. After mixing in the internal mixer, the internal mixer is evacuated to a vacuum state, and the internal pressure of the internal mixer is maintained at 30kPa. After maintaining pressure and defoaming for 40 minutes, the normal pressure is restored, and high-strength thermal insulation building coatings are obtained after natural cooling at room temperature.
[0030] Example 2
[0031] The preparation method of this embodiment is as follows: A high-strength thermal insulation building paint is composed of the following raw materials in parts by weight: 90 parts of polyurethane resin, 20 parts of phenolic resin, 25 parts of water, 3 parts of perfluoropropyl vinyl ether, 9 parts of thickener, 10 parts of functional additive, 6 parts of cross-linking agent, 5 parts of film-forming agent, 1.5 parts of isolating agent, 0.4 parts of reinforcing agent and 0.25 parts of catalyst.
[0032] The preparation method of the functional additive comprises the following steps: Step 1, soaking the modified aluminum silicate fiber in a 0.11 mol / L hydrogen chloride aqueous solution for 7 hours, completing the pretreatment of the modified aluminum silicate fiber after soaking, and continuing to soak the modified aluminum silicate fiber in a 1.1 mol / L caustic soda solution. During the soaking process, the fiber is placed in an oven at 90°C for 7 hours, and after high-temperature soaking, the modified aluminum silicate fiber treated with alkali etching is obtained; Step 2: Cut the modified aluminum silicate fiber obtained by alkali etching in step 1 into pieces, wash with boiling water for 50 minutes, and then place it in an oven at 60°C for 2.2 hours. Mix dimethylacetamide as a solvent with the small pieces of modified aluminum silicate fiber at a solid-liquid ratio of 1:35. Keep the solvent temperature at 70°C and dissolve for 60 minutes. After dissolution, a modified aluminum silicate fiber solution is obtained, which is the functional additive.
[0033] Furthermore, the preparation method of modified aluminum silicate fiber is as follows: select aluminum silicate fiber with a fiber length of 1450μm and a pH value of 8.5, place the aluminum silicate fiber in a sodium hydroxide solution with a solid-liquid ratio of 1:32, and perform high-temperature treatment on the mixed solution. The high-temperature treatment temperature is controlled at 85°C, and then placed in an oven and dried at 55°C for 1.2h. After the drying treatment is completed, wash with water for use, thereby obtaining a base material, and then place the base material in an acrylamide-methylpropane sulfonic acid reaction solution at a solid-liquid ratio of 1:3.5, and carry out a water bath at 80°C for 11 minutes. After washing with water and freeze-drying, the obtained product is the modified aluminum silicate fiber.
[0034] Furthermore, the preparation method of the isolation agent is as follows: add mullite powder as powder to a mixing device, add 1.2 times the amount of water and 0.25 times the amount of water glass to the mixing device, start the mixing device and stir at high speed for 17 minutes, after the mixing device obtains slurry, pour the slurry into a 15mm×15mm×1mm mold for molding preparation, dry and solidify the mold in batches, place multiple batches of molds in a drying oven set at 55°C for 48 hours for drying and solidification, and after drying and solidification, place the obtained dried and solidified material in a kiln at 1300°C and burn it for 9 hours to finally obtain a flaky solid raw material.
[0035] Furthermore, the solid raw material is added into the grinding chamber of the ball mill, the ball mill is started and the ball mill is continuously milled for 35 minutes at a speed of 500 r / min, the powder obtained after ball milling is placed in a mixing device, 2.5 times the amount of water as the powder is added, and then the mixing device is started at a low speed and stirred for 6 minutes. After stirring, the powder and water are evenly mixed to obtain a mud material, which is the isolation agent.
[0036] Furthermore, the preparation method of the thickener is: diatomaceous earth, sodium polyacrylate, ethoxylated carbamate and agar are mixed and poured into a mixing device and stirred at a low speed for 17 minutes. After the stirring is completed, a 300-mesh filter cloth is used to filter to obtain the thickener.
[0037] The cross-linking agent is tetramethylethylenediamine solution, and the reinforcing agent is methacrylate.
[0038] The catalyst is benzodiazepine, and the film-forming agent is acrylic resin.
[0039] Furthermore, the catalyst is processed as follows: the catalyst raw material is added into a high-speed disperser, and then the speed of the high-speed disperser is controlled to 850 r / min, the time is controlled to 6 min, and then the pressure is reduced, and the pressure reduction rate is controlled at 5 kPa / min until it returns to normal pressure, thereby obtaining the catalyst.
[0040] In addition, the present embodiment also provides a method for preparing the above-mentioned high-strength thermal insulation building coating, comprising the following steps: mixing the polyurethane resin and the phenolic resin and adding them to an internal mixer, preheating the mixture after adding them to the internal mixer, the preheating temperature is 140°C, keeping warm for 3 hours after the preheating is completed, running the internal mixer for heat preservation and mixing for 2.2 hours after heat preservation, then stopping and continuing to heat up to 185°C, and continuing to keep warm and mix for 3.2 hours after heating, the resulting coating base material is used for standby, and the mixed thickener, functional additive and cross-linking agent are heated in a constant temperature water bath at 95°C, and the constant temperature heating time is 2 hours. The mixing time is set to 35 minutes, thereby obtaining the additive, and then the coating base material, additive and other raw materials are weighed as needed, and each raw material is put into the internal mixer. Each raw material is preheated to 150°C in the internal mixer. After the preheating is completed, the internal mixer is set to a speed of 350r / min and started. After heat preservation and mixing for 1.2 hours, a preliminary mixture is obtained. After mixing in the internal mixer, the internal mixer is evacuated to a vacuum state, and the internal pressure of the internal mixer is maintained at 31kPa. After maintaining pressure and defoaming for 42 minutes, the normal pressure is restored, and high-strength thermal insulation building coatings are obtained after natural cooling at room temperature.
[0041] Example 3
[0042] The preparation method of this embodiment is as follows: A high-strength thermal insulation building paint is composed of the following raw materials in parts by weight: 100 parts of polyurethane resin, 25 parts of phenolic resin, 30 parts of water, 4 parts of perfluoropropyl vinyl ether, 10 parts of thickener, 12 parts of functional additive, 8 parts of cross-linking agent, 6 parts of film-forming agent, 1.8 parts of isolating agent, 0.6 parts of reinforcing agent and 0.3 parts of catalyst.
[0043] The preparation method of the functional additive comprises the following steps: Step 1, soaking the modified aluminum silicate fiber in a 0.12 mol / L hydrogen chloride aqueous solution for 8 hours, completing the pretreatment of the modified aluminum silicate fiber after soaking, and continuing to soak the modified aluminum silicate fiber in a 1.2 mol / L caustic soda solution. During the soaking process, the fiber is placed in an oven at 100°C for 8 hours, and after high-temperature soaking, the modified aluminum silicate fiber treated with alkali etching is obtained; Step 2: Cut the modified aluminum silicate fiber obtained by alkali etching in step 1 into pieces, wash with boiling water for 60 minutes, and then place in an oven at 60°C for drying for 2.5 hours. Mix dimethylacetamide as a solvent with the small pieces of modified aluminum silicate fiber at a solid-liquid ratio of 1:40. Keep the solvent temperature at 70°C for 70 minutes to obtain a modified aluminum silicate fiber solution, which is a functional additive.
[0044] Furthermore, the preparation method of modified aluminum silicate fiber is as follows: select aluminum silicate fiber with a fiber length of 1500μm and a pH value of 9, place the aluminum silicate fiber in a sodium hydroxide solution with a solid-liquid ratio of 1:35, and perform high-temperature treatment on the mixed solution. The high-temperature treatment temperature is controlled at 90°C, and then placed in an oven and dried at 60°C for 1.5h. After the drying treatment is completed, wash with water for use, thereby obtaining a base material, and then place the base material in an acrylamide-methylpropane sulfonic acid reaction solution at a solid-liquid ratio of 1:4, and water bath it at 85°C for 12 minutes. After washing with water and freeze-drying, the obtained product is the modified aluminum silicate fiber.
[0045] Furthermore, the preparation method of the isolation agent is as follows: add mullite powder as powder to a mixing device, add 1.5 times the amount of water and 0.3 times the amount of water glass to the mixing device, start the mixing device for high-speed stirring for 20 minutes, and after the mixing device obtains a slurry, pour the slurry into a 15mm×15mm×1mm mold for molding preparation, dry and solidify the mold in batches, place multiple batches of molds in a drying oven set at 60°C for 48 hours for drying and solidification, and after drying and solidification, place the obtained dried and solidified material in a kiln at 1300°C and burn it for 10 hours to finally obtain a flaky solid raw material.
[0046] Furthermore, the solid raw material is added into the grinding chamber of the ball mill, the ball mill is started and the ball mill is continuously milled for 40 minutes at a speed of 600 r / min, the powder obtained after the ball milling is placed in a mixing device, water 3 times the amount of the powder is added, and then the mixing device is started at a low speed and stirred for 8 minutes. After stirring, the powder and water are evenly mixed to obtain a mud material, which is the isolation agent.
[0047] Furthermore, the preparation method of the thickener is: diatomaceous earth, sodium polyacrylate, ethoxylated carbamate and agar are mixed and poured into a mixing device and stirred at a low speed for 20 minutes. After the stirring is completed, a 300-mesh filter cloth is used to filter and obtain the thickener.
[0048] The cross-linking agent is a hydrochloric acid solution, and the reinforcing agent is methacrylate.
[0049] The catalyst is hydroxybenzimidazole, and the film-forming agent is dimethylsiloxane copolymer.
[0050] Furthermore, the catalyst is processed as follows: the catalyst raw material is added into a high-speed disperser, and then the speed of the high-speed disperser is controlled to 900 r / min, the time is controlled to 8 min, and then the pressure is reduced, and the pressure reduction rate is controlled at 6 kPa / min until it returns to normal pressure, thereby obtaining the catalyst.
[0051] In addition, the present embodiment also provides a method for preparing the above-mentioned high-strength thermal insulation building coating, comprising the following steps: mixing the polyurethane resin and the phenolic resin and adding them to an internal mixer, preheating the mixture after adding them to the internal mixer, the preheating temperature is 150°C, keeping warm for 4 hours after the preheating is completed, running the internal mixer for heat preservation and mixing for 2.5 hours after heat preservation, then stopping and continuing to heat up to 190°C, and continuing to keep warm and mix for 3.5 hours after heating, the resulting coating base material is used for standby, and the mixed thickener, functional additive and cross-linking agent are heated in a constant temperature water bath at 100°C, and the constant temperature heating time is The mixing time is set to 40 minutes, thereby obtaining the additive, and then the coating base material, additive and other raw materials are weighed as needed, and each raw material is put into the internal mixer. Each raw material is preheated to 160°C in the internal mixer. After the preheating is completed, the internal mixer is set to a speed of 400r / min and started. After heat preservation and mixing for 1.5 hours, a preliminary mixture is obtained. After mixing in the internal mixer, the internal mixer is evacuated to a vacuum state, and the internal pressure of the internal mixer is maintained at 32kPa. After pressure maintenance and defoaming for 45 minutes, the normal pressure is restored, and high-strength thermal insulation building coatings are obtained after natural cooling at room temperature.
[0052] Comparative Example 1: The difference between this embodiment and embodiment 1 is that this embodiment uses an equal amount of aluminum silicate fiber solution to replace the functional additive.
[0053] Comparative Example 2: The difference between this embodiment and embodiment 1 is that this embodiment does not contain a release agent.
[0054] Comparative Example 3: The difference between this embodiment and embodiment 1 is that in this embodiment, no alkaline etching treatment is performed when preparing the functional additive.
[0055] Comparative Example 4: The difference between this embodiment and embodiment 1 is that this embodiment does not contain a functional auxiliary agent.
[0056] Performance test: The relevant properties of the architectural coating samples provided in Examples 1-3 and Comparative Examples 1-4 were tested respectively, and the obtained test data were recorded in the following table:
[0057] By comparing and analyzing the relevant data in the table, it can be seen that the architectural coating prepared by the present invention not only has good thermal insulation performance, but also has excellent hardness performance, which effectively improves its use effect while also ensuring its quality. This shows that the high-strength thermal insulation architectural coating and its preparation method provided by the present invention have a broader market prospect and are more suitable for promotion.
[0058] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0059] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A high-strength thermal insulation architectural coating, characterized in that: The invention is composed of the following raw materials in parts by weight: 80-100 parts of polyurethane resin, 15-25 parts of phenolic resin, 20-30 parts of water, 2-4 parts of perfluoropropyl vinyl ether, 8-10 parts of thickener, 8-12 parts of functional additive, 5-8 parts of crosslinking agent, 4-6 parts of film-forming agent, 1.2-1.8 parts of isolating agent, 0.3-0.6 parts of reinforcing agent and 0.2-0.3 parts of catalyst.
2. A high-strength thermal insulation architectural coating according to claim 1, characterized in that: The preparation method of the functional additive comprises the following steps: Step 1, soaking the modified aluminum silicate fiber in a 0.1-0.12 mol / L hydrogen chloride aqueous solution for 6-8 hours, completing the pretreatment of the modified aluminum silicate fiber after soaking, and continuing to soak the modified aluminum silicate fiber in a 1-1.2 mol / L caustic soda solution, and during the soaking process, placing it in an oven at 80-100°C for 6-8 hours, and obtaining the modified aluminum silicate fiber treated with alkali etching after high temperature soaking; Step 2: Cut the modified aluminum silicate fiber obtained by alkali etching in step 1 into pieces, wash with boiling water for 40-60 minutes, and then place it in an oven at 60°C for drying for 2-2.5 hours. Mix dimethylacetamide as a solvent with the small pieces of modified aluminum silicate fiber at a solid-liquid ratio of 1:30-40, maintain the solvent temperature at 70°C and dissolve for 50-70 minutes. After dissolution, a modified aluminum silicate fiber solution is obtained, which is the functional additive.
3. A high-strength thermal insulation architectural coating according to claim 2, characterized in that: The preparation method of the modified aluminum silicate fiber is as follows: aluminum silicate fiber with a fiber length of 1400-1500 μm and a pH value of 8-9 is selected, the aluminum silicate fiber is placed in a sodium hydroxide solution with a solid-liquid ratio of 1:30-35, the mixed solution is subjected to high-temperature treatment, the high-temperature treatment temperature is controlled at 80-90° C., then the mixed solution is placed in an oven with a temperature of 50-60° C. and dried for 1-1.5 hours, and washed with water for standby use after the drying treatment is completed, thereby obtaining a base material, and then the base material is placed in an acrylamide-methylpropane sulfonic acid reaction solution at a solid-liquid ratio of 1:3-4, and a water bath is carried out at 75-85° C. for 10-12 minutes, and the obtained product after washing with water and freeze-drying is the modified aluminum silicate fiber.
4. A high-strength thermal insulation architectural coating according to claim 1, characterized in that: The preparation method of the release agent is as follows: adding mullite powder as powder to a mixing device, adding 1-1.5 times of water and 0.2-0.3 times of water glass to the mixing device, starting the mixing device for high-speed stirring for 15-20 minutes, and after the mixing device obtains slurry, pouring the slurry into a 15mm×15mm×1mm mold for molding, drying and curing the mold in batches, placing multiple batches of molds in a drying oven set at 50-60°C for 48 hours for drying and curing, and after drying and curing, The dried and solidified material is placed in a kiln at 1300°C and fired for 8-10 hours to finally obtain a flaky solid raw material. The solid raw material is added to the grinding chamber of a ball mill, and the ball mill is started and continuously ball-milled for 30-40 minutes at a speed of 400-600r / min. The powder obtained after ball milling is placed in a mixing device, and water 2-3 times the amount of the powder is added. The mixing device is then started and stirred at a low speed for 5-8 minutes. After stirring, the powder and water are evenly mixed to obtain a mud material, which is the isolation agent.
5. The high-strength thermal insulation architectural coating according to claim 1, characterized in that: The preparation method of the thickener is as follows: diatomaceous earth, sodium polyacrylate, ethoxylated carbamate and agar are mixed and poured into a mixing device and stirred at a low speed for 15-20 minutes. After the stirring is completed, a 300-mesh filter cloth is used to filter to obtain the thickener.
6. The high-strength thermal insulation architectural coating according to claim 1, characterized in that: The cross-linking agent is selected from any one of ferric chloride aqueous solution, tetramethylethylenediamine solution, and hydrochloric acid solution, and the strengthening agent is selected from any one of polyacrylate and methacrylate.
7. The high-strength thermal insulation architectural coating according to claim 1, characterized in that: The catalyst is selected from any one of hydroxyphenyl triazine, benzodiazole, and hydroxybenzimidazole, and the film-forming agent is selected from any one of trimethylsiloxysilicate, acrylic resin, and dimethylsiloxane copolymer.
8. A high-strength thermal insulation architectural coating according to claim 7, characterized in that: The catalyst is processed as follows: the catalyst raw material is added into a high-speed disperser, and then the speed of the high-speed disperser is controlled to 800-900r / min, the time is controlled to 5-8min, and then the pressure is reduced, and the pressure reduction speed is controlled at 4-6kPa / min until it returns to normal pressure, thereby obtaining the catalyst.
9. A method for preparing a high-strength thermal insulation architectural coating according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing polyurethane resin and phenolic resin and adding them to an internal mixer; preheating the mixture after adding them to the internal mixer; keeping the mixture at 130-150°C; keeping the mixture at 2-4 hours after preheating; running the internal mixer for 2-2.5 hours of heat preservation and mixing; then stopping the machine and continuing to heat the mixture to 180-190°C; and continuing to heat the mixture for 3-3.5 hours after heating. The obtained coating base material is used for standby; mixing the thickener, functional additive and crosslinking agent and heating the mixture in a constant temperature water bath at 90-100°C; and setting the constant temperature heating time to 30-40 minutes. Additives, then weigh the coating base, additives and other raw materials as needed, put all the raw materials into the internal mixer, preheat all the raw materials to 140-160°C in the internal mixer, set the internal mixer speed to 300-400r / min after preheating, start, and obtain a preliminary mixture after heat preservation and mixing for 1-1.5h. After mixing in the internal mixer, evacuate the internal mixer to a vacuum state, maintain the internal pressure of the internal mixer at 30-32kPa, maintain pressure and defoam for 40-45min, then restore normal pressure, and obtain high-strength thermal insulation building coatings after natural cooling at room temperature.
Citation Information
Patent Citations
Preparation method of building coating
CN108300152A
Waterproof paint for single aluminum plate of curtain wall and preparation method thereof
CN109897431A